Antibacterial activity of ethanol extracts of hibiscus tiliaceus l. leaves from different extraction methods against Escherichia coli and Staphylococcus aureus - Devi Nisa Hidayati; Hanik Rohmatul Maghfiroh; Aysah Safitri (Universitas Ahmad Dahlan, 2023)
The leaves of sea hibiscus (Hibiscus tiliaceus L.) are known to have good antibacterial activity against Escherichia coli and Staphylococcus aureus, which is associated with the saponin, flavonoid, polyphenol, and tannin contents. Chemical compounds in plant extracts are, however, influenced by the extraction method used. This study aimed to determine the antibacterial activity of the ethanol extracts of Hibiscus tiliaceus L. leaves obtained using four different extraction methods against E. coli and S. aureus. In the maceration, percolation, reflux, or Soxhlet method, 200 g of the crude drug (i.e., dried sea hibiscus leaf powder) was extracted with 96% ethanol, and the derived extract was tested at 1%, 2%, 3%, 4%, and 5% concentrations. The disk diffusion method was used to test the antibacterial activity by observing and statistically analyzing the diameter of the zones of inhibition. Results showed that all the ethanol extracts have antibacterial properties against E. coli and S. aureus,with the maceration-produced extract forming significantly different zones of inhibition from the other methods (percolation, reflux, and the Soxhlet) at all concentrations.